(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Hydrothermal dolomitization (HTD) is a major diagenetic process of carbonate rocks, significantly impacting on reservoir storage, reservoir quantity, and hydrocarbon migration. This paper adds a new insight in contrasting HTD mechanisms under shallow and subsurface deep settings, and focuses on dolomite characterization and properties in the Cretaceous Qamchuqa Formation. Shallow burial HTD produced four phases of saddle dolomites, SDI, SDII, SDIII, and SDIV. The deep burial HTD at least shows one type of saddle dolomitization phase “SDs”. The hydrothermal dolomitization in shallow system, which is related to an open system, offers growth of large, well-formed dolomite crystals, forming massive dolomite bodies due to high fluid-rock interaction. In contrast, deep burial HTD occurring under elevated temperature, is primarily driven by low fluid-rock interaction in a semi-open system. The semi-open system requires a high pressure that deformed the SD formation, which is coincide with an increasing of the vertical stress. As a result, the SD formation is a transfer from a ductile phase to a brittle deformation, and led to an in-situ saddle brecciation, facilitating the creation of conduit for fluid/hydrocarbon migration.